In situ high-resolution XPS studies on adsorption of NO on Pt(1 1 1) - Zhu, Junfa; Kinne, Martin; Fuhrmann, Thomas; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2003)
High-resolution X-ray photoelectron spectroscopy (XPS) and temperature-programmed XPS at BESSY II have been applied to investigate the adsorption and desorption of NO on a Pt(1 1 1) surface. The coverage and temperature-dependent bonding configurations of NO have been identified from adsorbate O 1s and substrate Pt 4f core-level photoemission spectra, which were collected in situ during NO uptake or heating with data collection times per spectrum between 4 and 7 s. At 110 K, NO molecularly adsorbs on Pt(1 1 1) and sequentially populates three different adsorption sites. Up to coverages of 0.25 ML, only fcc-hollow sites are occupied, leading to the formation of a (2 × 2)-NO adsorbate structure. As coverage increases, in addition on-top sites are populated until at 0.5 ML a (2 × 2)-2NO structure is formed, which also represents the saturation structure at 250 K. Further increasing the coverage at 110 K leads to the occupation of hcp-hollow sites; at saturation, a (2 × 2)-3NO structure is observed with a coverage of 0.75 ML. Upon heating, the desorption of NO from the hcp-hollow sites gives rise to a desorption peak at 190 K. Further heating induces the desorption of on-top NO species starting at 275 K and fcc-hollow NO species starting at 320 K. No dissociation takes place. © 2003 Elsevier Science B.V. All rights reserved.